A Low-Cost Automated Test Column to Estimate Soil Hydraulic Characteristics in Unsaturated Porous Media. (24th January 2017) - Salas-García, J.; Garfias, J.; Martel, R.; Bibiano-Cruz, L.
Abstract : The estimation of soil hydraulic properties in the vadose zone has some issues, such as accuracy, acquisition time, and cost. In this study, an inexpensive automated test column (ATC) was developed to characterize water flow in a homogeneous unsaturated porous medium by the simultaneous estimation of three hydraulic state variables: water content, matric potential, and water flow rates. The ATC includes five electrical resistance probes, two minitensiometers, and a drop counter, which were tested with infiltration tests using the Hydrus-1D model. The results show that calibrations of electrical resistance probes reasonably match with similar studies, and the maximum error of calibration of the tensiometers was 4.6% with respect to the full range. Data measured by the drop counter installed in the ATC exhibited a high consistency with the electrical resistance probes, which provides an independent verification of the model and indicates an evaluation of the water mass balance. The study results show good performance of the model against the infiltration tests, which suggests a robustness of the methodology developed in this study. An extension to the applicability of this system could be successfully used in low-budget projects in large-scale field experiments, which may be correlated with resistivity changes.